Pengaruh Pertumbuhan Laba, Profitabilitas dan Ukuran Perusahaan Pada Kualitas Laba - Sumertiasih, Ni Putu Lia; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2022)
The purpose of the study was to examine the effect of profit growth, profitability, and firm size on earnings quality. The population studied in the study were all manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2019 period with a total of 156 manufacturing companies. The sample used in this study was determined by purposive sampling method with 3 criteria. Based on these criteria, a sample of 39 companies was obtained with 3 years of observation so that the total sample studied became 117 observational data. The data analysis technique used in this research is multiple linear regression analysis. The results showed that profit growth, profitability, and firm size had a positive effect on earnings quality. Keywords: Earnings Quality; ROA; SIZE; Growth.